Improving Greenhouse Heating in Portugal - Meneses, J.F. (2011)
Although several new solutions for greenhouse heating and environmental control are being investigated all over the world; to reduce energy consumption and environmental impacts, to increase the efficiency of energy use for plant production in protected cultivation or to take advantage of the new renewable energy sources, in Portugal the great majority of producers still rely on more conventional heating systems for an economical year round production of vegetables and flowers. The objective of this work is to review some guidelines to help the grower when choosing the best heating solutions for different crops and cultivation systems. First, the level of heating required is defined and the correspondent heating power is analysed. Secondly, the main heating systems are mentioned including their components, characteristics, effects on greenhouse climate, soil and plant temperature. Relative costs of equipment and energy consumption are analyzed and some examples of practical solutions are presented from vegetable and flower production growers. Finally, several strategies to reduce the energy required for greenhouse heating are given and studied, including greenhouse structures, covering materials, thermal screens, air temperature and humidity control.